The Ability of Elementary School Teacher Education Program Students in Designing Online Learning Scenario Using Problem-Based Learning Model - Laila Rahmawati; Novia Siswandari; Muthia Farida (IAHN-TP Palangka Raya, 2022)
Designing learning using learning scenario must be mastered by teacher in terms of the theoretical elements in it. Today teachers need to learn how to design learning scenario that is adaptable to the conditions of online learning by applying problem solving skills using a problem based learning model. Online learning scenario also needs to be designed to match the demands of abilities in the 21st century, namely learning and innovation skills, life and skills, and digital literacy. This study uses a mix method design that combines quantitative and qualitative designs at a simple level (Concurrent Mix Method). The population of this study was the 3rd semester of Elementary School Teacher Education Program (PGSD) students by taking a sample of 75 people through purposive sampling technique. The research assessment instrument used an assessment indicator for making online learning scenario adapted to the syntax of the Problem Based Learning model. The findings and results of the research showed that there were still many students who were not skilled in preparing online learning scenario with Problem Based Learning model. It can be seen by only 5% of students who had very high ability in making learning scenario, 29% were categorized to those who had high ability, while 21% were categories to those who had average ability; and 44% belonged to the category of having low ability. This low ability was seen from the aspects of making KKO and adjusting ABCD elements to learning objectives and making final learning activities that still need to be improved. These results can be the reference for both the teachers and the students that in the future the PGSD students can further improve their skills and abilities in designing online learning scenario for the implementation of effective, innovative and meaningful learning in accordance with the demands of the 21st century. Keywords : Learning Scenario, Online, Problem Based Learning